Effect of transcutenous electrical nerve stimulation on micro-circulation in chronic leg ulcer - Ayman Shaban Somida Goda; Eman Mohamed Othman; Mohamed Mahmoud Abdelkhalek Khallaf; Wael Naem Thabeet (Cairo : Ayman Shaban Somida Goda, 2017)
Purpose : The current study was conducted to investigate the therapeutic efficacy of transcutenous electrical nerve stimulation on micro-circulation in chronic leg ulcer. Subjects and Methods: Forty (17 males and 23females) patients who had leg venous ulcer. They were complaining from delayed wound healing due to poor blood flow. The duration of ulcer was ranged from 3 to 6 months. The patients were selected from Department of Surgery in El kasr Al ainy Hospital. Their ages were ranged from 40- 60 years. Patients were classified into two equal groups (20 patients for each group).Group(A): (Transcutaneous electrical nerve stimulation group):Twenty patients who had chronic leg venous ulcer and they were received low frequency TENS (2H3, 10- 45 mA) for 60 minutes three times every week, for 3 months and they were received the regular wound care in form of regular changing dressing. Group (B):Twenty patients who had leg venous ulcer and they were received the regular wound care in form of regular changing dressing. Results: This study showed a significant improvement in laser doppler imaging (mmhg) with percentage of 25 % after three months of treatment application when compared between before treatment and pre-treatment. Conclusion: Usage of transcutenous electrical nerve stimulation produce objective improvement in microcirculation on chronic leg ulcer
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Surgery
Issued also as CD
Keywords: Chronic leg ulcer; Microcirculation; Physical therapy